Impact of Lesion Load Thresholds on Alberta Stroke Program Early Computed Tomographic Score in Diffusion-Weighted Imaging - Schröder, Julian; Cheng, Bastian; Malherbe, Caroline; Ebinger, Martin; Köhrmann, Martin; Wu, Ona; Kang, Dong-Wha; Liebeskind, David S.; Tourdias, Thomas; Singer, Oliver C.; Campbell, Bruce; Luby, Marie; et al. (Frontiers in Neurology, 2018)
Background and Aims: Assessment of ischemic lesions on CT or MRI diffusion weighted imaging (DWI) using the Alberta Stroke Program Early CT Score (ASPECTS) is widely used to guide acute stroke treatment. However, it has never been defined how many voxels need to be affected to label an DWI-ASPECTS region ischemic. We aimed to assess the effect of various lesion load thresholds on DWI-ASPECTS and compare this automated analysis with visual rating. Materials and Methods: We analyzed overlap of individual DWI lesions of 315 patients from the previously published PRE-FLAIR study with a probabilistic ASPECTS template derived from 221 CT images. We applied multiple lesion load thresholds per DWI-ASPECTS region (>0, >1%, >10%, >20% in each DWI-ASPECTS region) to compute DWI-ASPECTS for each patient and compared the results to visual reading by an experienced stroke neurologist. Results: By visual rating, median ASPECTS was 9, 84 patients had an DWI-ASPECTS score ≤7. Mean DWI lesion volume was 22.1 (±35) ml. In contrast, by use of >0, >1%-, >10%-, and >20%-thresholds, median DWI-ASPECTS was 1, 5, 8 and 10; 97.1% (306), 72.7% (229), 41% (129) and 25.7% (81) had DWI-ASPECTS ≤7, respectively. Overall agreement between automated assessment and visual rating was low for every threshold used (>0%: κw=0.020 1%: κw=0.151; 10%: κw=0.386; 20% κw=0.381). Agreement for dichotomized DWI-ASPECTS ranged from fair to substantial (≤7: >10% κ=0.48; >20% κ=0.45; ≤5: >10% κ=0.528; >20% κ=0.695). Conclusion: Overall agreement between automated and the standardly used visual scoring is low regardless of the lesion load threshold used. However, dichotomized scoring achieved more comparable results. Varying lesion load thresholds had a critical impact on patient selection by ASPECTS. Of note, the relatively low lesion volume and lack of patients with large artery occlusion in our cohort may limit generalizability of these findings.